Impacts of double-fortified salt on anemia and cognition: Four-year follow-up evidence from a school-based nutrition intervention in India - Liza von Grafenstein; Abhijeet Kumar; Santosh Kumar; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2021)
Long-term follow-up of early childhood health interventions is important for human capital accumulation. We provide experimental evidence on child health and human capital outcomes from the longer-term follow-up of a school-based nutrition intervention in India. Using panel data, we examine the effectiveness of the use of iron and iodine fortified salt in school lunches to reduce anemia among school children. After four years of treatment, treated children, on average, have higher hemoglobin levels and a lower likelihood of anemia relative to the control group. Interestingly, the intervention did not have an impact on cognitive and educational outcomes.
Keywords: C93; I15; I18; O12; 330; Child health; double-fortified salt; India; school feeding